Answer:
y=-100x+700
Step-by-step explanation:
Slope=Rise/Run=Δy/Δx=(y₂-y1)/(x₂-x₁)=(200-600)/(5-1)=(-400)/(4)=-100
So your slope would be m=-100
To find b, the y-intercept, we plug in a given output of y for a given input of x and solve for b:
y=mx+b (Slope-intercept form)
y=-100x+b (Equation so far)
200=-100(5)+b [Plugging in (5,200)]
200=-500+b
700=b
So since the y-intercept is b=700, then the equation of the line is y=-100x+700
Answer:
Parent's share would be : 28%
Step-by-step explanation:
Cost of the computer = $2000
Anya's share = $1200
Brother's share = $240
Parents paid rest. That will be : 2000 - 1200 - 240 = $560
Percentage of parents share :
![\frac{560}{2000} \times 100 = 28 \%](https://tex.z-dn.net/?f=%5Cfrac%7B560%7D%7B2000%7D%20%5Ctimes%20100%20%3D%2028%20%5C%25)
Answer:
99/34 i believe
Step-by-step explanation:
In order to solve this we'll start by assigning variables to hamburgers and cheeseburgers, since these are what we're trying to find. Lets say x = hamburgers and y = cheeseburgers. So we know two things, we know that x+y= 763 (hamburgers plus cheeseburgers sold equals 763, and we know that y= x+63 (cheeseburgers sold equals 63 more than hamburgers sold). Now we have a system of equations. This can be solved most easily by rearranging each equation to each y, and then set them equal to each other:
x+y=763 -> y=763-x, and we already have y=x+63. Set them equal to each other:
x+63 = 763-x (add x to both sides) -> 2x+63 = 763 (subtract 63 from both sides) -> 2x = 700 (divide both sides by 2) x = 350. So we solved for x, which is hamburgers sold, which is what the question asks for, so your answer is 350 hamburgers were sold on Saturday
Answer:
(- 1, - 2 )
Step-by-step explanation:
Given the 2 equations
x - 3y = 5 → (1)
5x - 2y = - 1 → (2)
Rearrange (1) expressing x in terms of y by adding 3y to both sides
x = 5 + 3y → (3)
Substitute x = 5 + 3y in (2)
5(5 + 3y) - 2y = - 1 ← distribute left side
25 + 15y - 2y = - 1
25 + 13y = - 1 ( subtract 25 from both sides )
13y = - 26 ( divide both sides by 13 )
y = - 2
Substitute y = - 2 in (3) for corresponding value of x
x = 5 + (3 × - 2) = 5 - 6 = - 1
Solution is (- 1, - 2 )